(untitled) (Latakia University Journal -Biological Sciences Series, 2020)
This research dealt, with the production of live food composed of green monocyte alga Tetraselmis sp. which is suitable for growth of adult individuals and larvae of pearl oyster Pinctada radiata, and the determination of the appropriate food concentrations for adults and larvae during breeding and hatching in vitro. The required alga was isolated from marine water in the Afamia Region of the Lattakia Coast, and culture using the medium of solid agar, in addition to the media of nutrient stock F/2 (15 – 30) day before the transfer of adults to the breeding tanks in the laboratory. The average number of algal cells of Tetraselmis sp. ranged between 9.17X104 on the first day of the brood and 100X104 on the day 15, while the highest value was on the day 10 with an average 144.17X104. The daily ration from the alga cells for one adult was0.1176 g equivalent to 408 ml from the algal suspension, while the daily feeding volume of the larvae ranged between 21 – 33 ml for 6 L tank. تناول هذا البحث إنتاج الغذاء الحيّ المؤلف من الطّحلب الأخضر وحيد الخلية Tetraselmis sp. المناسب لنموّ أفراد ويرقات محار اللؤلؤ Pinctada radiata، وتحديد التراكيز المناسبة الواجب إضافتها لكل من الأفراد البالغة واليرقات أثناء التربية والتفريح مخبرياً. تمّ عزل الطّحلب المطلوب للتغذية من المياه البحرية في منطقة أفاميا من ساحل مدينة اللاذقية، وتنّميته باستخدام وسط الآغار الصلب، بالإضافة إلى مخزون الأملاح المغذّية F/2، قبل (15 – 30) يوم من نقل الأفراد البالغة إلى أحواض التربية في المختبر. تراوح متوسط عدد الخلايا الطحلبية لـ Tetraselmis sp. بين 9.17X104 في اليوم الأول من الحضن و 100X104 في اليوم الخامس عشر، بينما كانت القيمة العليا في اليوم العاشر إذ بلغ المتوسط .144.17X104 بلغت الوجبة اليومية للفرد البالغ الواحد من الخلايا الطحلبية 0.1176 غ أي ما يعادل 408 مل من المعلّق الطّحلبي، بينما تراوح حجم التغذية اليومي لليرقات بين 21 – 33 مل لحوض سعة 6 ل.